2020
DOI: 10.2352/issn.2169-4451.2020.36.69
|View full text |Cite
|
Sign up to set email alerts
|

3D Halftoning based on Iterative Method Controlling Dot Placement

Abstract: Realistic appearance reproduction is of great importance in 3D printing's applications. Halftoning as a necessary process in printing has a great impact on creating visually pleasant appearance. In this article, we study the aspects of adapting and applying Iterative Method Controlling Dot Placement (IMCDP) to halftone three-dimensional surfaces. Our main goal is to extend the 2D algorithm to a 3D halftoning approach with minor modifications. The results show high-quality reproduction for all gray tones. The 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…The original IMCDP algorithm has been extended to 3D domain in Ref. [40] and the effect of applying variable halftone structures based on the spatial information has shown that different halftone structures could be used to control the reproduction of details [24,41]. As a next step, we are planning to develop an adaptive structure-aware 3D color halftoning algorithm, which has all the reproduction qualities of IMCDP while being aware of the color and geometry of the 3D object.…”
Section: Discussionmentioning
confidence: 99%
“…The original IMCDP algorithm has been extended to 3D domain in Ref. [40] and the effect of applying variable halftone structures based on the spatial information has shown that different halftone structures could be used to control the reproduction of details [24,41]. As a next step, we are planning to develop an adaptive structure-aware 3D color halftoning algorithm, which has all the reproduction qualities of IMCDP while being aware of the color and geometry of the 3D object.…”
Section: Discussionmentioning
confidence: 99%
“…In [7], the extension of the two-dimensional IMCDP to a 3D halftoning method, called 3D IMCDP, is thoroughly described. In this section, a brief description of 3D IMCDP is given.…”
Section: D Imcdpmentioning
confidence: 99%
“…This will give one of them much more chance to be chosen as the maximum than the other one. This will cause undesirable halftone structure artifacts, as illustrated in [7]. In order to reduce this effect, instead of using a 3D Gaussian function, an 𝑚 × 𝑚 2D Gaussian function is designed and the weights are sorted in descending order.…”
Section: D Imcdpmentioning
confidence: 99%
See 1 more Smart Citation
“…In Ref. [17], an iterative 3D halftoning method, called 3D IMCDP was introduced, which is an extension of the 2D IMCDP halftoning method discussed in Ref. [2].…”
Section: Introductionmentioning
confidence: 99%